2021
DOI: 10.1037/pspa0000267
|View full text |Cite
|
Sign up to set email alerts
|

Awe, daily stress, and elevated life satisfaction.

Abstract: It is widely assumed that experiences of awe transform the meaning of daily stresses. Across six studies we tested whether and how the experience of awe is associated with reduced daily stress levels in the moment and, in so doing, leads to elevated life satisfaction. We first documented that individuals who tend to experience greater awe on a daily basis (Study 1) or who report higher levels of trait-like awe (Study 2) report lower levels of daily stress, even after controlling for other positive emotions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 149 publications
(275 reference statements)
4
60
0
Order By: Relevance
“…The results showed that positive awe increased the feeling of connectedness, which was consistent with much previous research (Bai et al, 2017;Krenzer et al, 2020;Nelson-Coffey et al, 2019;Shiota et al, 2007;Stellar et al, 2017;van Cappellen & Saroglou, 2012;Yaden et al, 2019). Previous research has also suggested that positive awe experience enhanced well-being through various psychological mechanisms (Anderson et al, 2018;Bai et al, 2021;Krause & Hayward, 2015;Rudd et al, 2012;Sturm et al, 2020;Zhao et al, 2019). According to a previous study (Krause & Hayward, 2015), our results showed that a sense of connection during positive awe experiences was positively correlated .18, .48] [.07, .39] [-.12, .21] [.24, .52] [.25, .53] [.29, .56] [.18, .48] [-.07, .26] [.27, .55] [.32, .58] [.22, .50] [.02, .34] [-.00, .32] [.23, .51] [.23, .52 with well-being, which suggested that the feelings of connection to someone/thing (i.e., others and oneness) was associated with the effects of awe on well-being.…”
Section: Connectionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results showed that positive awe increased the feeling of connectedness, which was consistent with much previous research (Bai et al, 2017;Krenzer et al, 2020;Nelson-Coffey et al, 2019;Shiota et al, 2007;Stellar et al, 2017;van Cappellen & Saroglou, 2012;Yaden et al, 2019). Previous research has also suggested that positive awe experience enhanced well-being through various psychological mechanisms (Anderson et al, 2018;Bai et al, 2021;Krause & Hayward, 2015;Rudd et al, 2012;Sturm et al, 2020;Zhao et al, 2019). According to a previous study (Krause & Hayward, 2015), our results showed that a sense of connection during positive awe experiences was positively correlated .18, .48] [.07, .39] [-.12, .21] [.24, .52] [.25, .53] [.29, .56] [.18, .48] [-.07, .26] [.27, .55] [.32, .58] [.22, .50] [.02, .34] [-.00, .32] [.23, .51] [.23, .52 with well-being, which suggested that the feelings of connection to someone/thing (i.e., others and oneness) was associated with the effects of awe on well-being.…”
Section: Connectionsupporting
confidence: 90%
“…Consistent with research suggesting that small self and dispositional awe are positively associated not only each other (Piff et al, 2015), but also with the feeling of connectedness and self-reported psychophysiological responses (Yaden et al 2019), connection, chills, and diminished self are positively associated with small self and dispositional awe. Additionally, many previous studies have demonstrated that positive-awe experiences increased subjective wellbeing (Anderson et al, 2018;Bai et al, 2021;Krause & Hayward, 2015;Rudd et al, 2012;Sturm et al, 2020;Zhao et al, 2019). In particular, feelings of awe positively predict life satisfaction through increased senses of connection to others (Krause & Hayward, 2015).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Positive psychology researchers proposed that awe, as a self-transcendent emotion, may promote individual wellbeing and personal change ( Haidt and Keltner, 2004 ), and awe experiences in daily life and in the laboratory led to greater momentary wellbeing (i.e., compared with no awe experience) ( Gordon et al, 2016 ). Awe could also reduce the negative impact of daily stress and negative emotions and improve life satisfaction ( Rudd et al, 2012 ; Bai et al, 2021 ). Therefore, as a positive emotion of self-transcendence, awe has a distinct emotional effect, which promotes the growth and transformation of primary school teachers and improves their life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, an increasing number of researchers have devoted their attention to highlight the effects of awe experiences on individuals. For example, awe has been found to diminish the sense of self (Bai et al, 2017;Sturm et al, 2020), and to promote spirituality (Saroglou et al, 2008;Van Cappellen and Saroglou, 2012), prosociality (Piff et al, 2015;Prade and Saroglou, 2016), humility (Stellar et al, 2018), environmentalism (Zhao et al, 2018), and well-being (Rudd et al, 2012;Bai et al, 2021). However, researchers who investigated awe, and how this emotion influence intraindividual and interpersonal changes, have primarily focused on the adult.…”
Section: Features Of Awementioning
confidence: 99%